Social media in supply chains and logistics: Contemporary trends and themes - Savvas Papagiannidis; Michael Bourlakis; Eric See-To (International Journal of Business Science & Applied Management (IJBSAM), 2019)
Although social media have been employed in various business and management scientific domains, their use and role in relation to supply chains has been scant. This paper addresses the gap and adds to this body of knowledge by providing new data and original insights and by showcasing emerging, contemporary trends and themes. Over a period of 4 months we downloaded tweets that contained the #supplychain and/or the #logistics hashtags. After cleaning the data and filtering tweets in English we analysed 76,378 posts, using different analytical techniques. Our work shows the key trends emerging where various supply chain management technologies play a dominant role. Blockchain is the leading technology followed by artificial intelligence. The increased role of last mile logistics is also shown which can be related to e-commerce and customer service. Supply chain technologies are also clustered and interlinked in a related dendrogram and, automation is linked to robots and robotics, analytics is linked to data, artificial intelligence is linked to IoT and machine learning. Similar interlinkages are illustrated for other trends impacting contemporary supply chains. This research provides direction to supply chain managers for the key trends and themes emerging in their profession, and a new graph-based measure to understand the topology of the social media mindset landscape. In turn, such trends can offer valuable insights as to how the industry is developing and help proactively identify areas of potential investment.
Keywords: 650; social media; tweets; contemporary trends and themes; supply chain management; logistics